Efektivitas Pijat Bayi terhadap Penambahan Berat Badan Bayi Usia 6-12 Bulan dengan Masalah Berat Badan di PMB M Desa Karyabakti Kecamatan Batujaya Karawang Tahun 2023 - Wiwit Desi Intarti; Maysaroh Suharningsih; Lenny Irmawaty Sirait (Jurnal Kebidanan Harapan Ibu Pekalongan, 2024)
Growth and development in infants is inseparable from the concept of growth and development. Body weight is the most important anthropometric measurement and is most often used in infants. Weight measurement is the most important measurement in examining a baby or toddler. Objective: The purpose of this study was to determine the effectiveness of infant massage on weight gain in infants aged 6-12 months. Methods: This research is a quantitative research using quasi-experimental methods. The research design used in this study was one group pretest posttest. The sampling technique used in this study was Total Sampling, which used the entire population of 25 people. The research instrument used was digital baby scales and observation sheets, namely demographic data questionnaires. Results: The results of the data obtained showed that there was an increase in the average body weight which previously had an average of 6.57 to 7.02. As many as 25 people (100%) experienced an increase in weight development. With the conclusion of the T test with p < 0.05. conclusion The results of this study indicate that there is an effect before and after giving baby massage for 7 interventions on increasing the weight of infants aged 6- 12 months at PMB M Karyabakti Village, Batujaya District, Karawang in 2023.